DEVELOPMENT OF FINITE ELEMENT ANALYSIS PROGRAM FOR ROTORDYNAMIC PREDICTION OF SINGLE AND MULTI DISK ROTOR MODEL - Muhammad Idris; Zakie Anugia; Donny Mustika (Indonesian Journal of Engineering and Science, 2022)
The rotating equipment is a crucial part of system performance reliability. Vibration, as a characteristic of an oscillating body, is a fundamental parameter to determine the dynamic behaviour of the rotor system. The dynamic characteristics include natural frequency, critical speed, mode shape, and vibration response. This paper discussed the application of rotordynamics analysis as a tool to numerically predict the dynamic behaviour of a rotor system. The aim is to determine a rotor system's natural frequency and critical speed by a finite element analysis (FEA) program. The selected method is validated using various analytical methods from other references with small discrepancies in the result. The calculation of FEA using the computational program; they applied the developed program to describe the dynamic characteristic of single and multi-disk rotors. The developed works provided comprehensive results about a rotor system's natural frequency, mode shape, and critical speed and predicted the vibration response due to unbalance. However, other types of rotors, such as coaxial dual rotors, can be further investigated to make the program capable of the general purpose of the rotor. Validation with the real case problem could be an interesting investigation to satisfy the result of developed works.